UJI COBA REKAYASA ALAT UKUR DIAMETER POHON DI HUTAN ALAM - Wesman Endom; Soenarno (BRIN Publishing, 2018)
Trial test of tree diameter measurement device ‘wesyano’ was conducted in 2016 at a natural forest in Central Kalimantan. This paper evaluates five main components of the measurement device: roller measurement, telescopic stick, frame shaft, lid-scale meter, scale-meter, and its locker. Result on single and double measurements showed that wesyano had an accuracy of 0.98–0.99 with an efficiency level of 1–4 times faster than the phi-band measurement. Validated results indicated that wesyano was highly correlated with phi-band measurement for single (r = 0.978) and double (r = 0.982) measurements. There is no significant differences between single and double measurements. The study indicates that wesyano could be used for phi-band measurement substitute. The device was more practice, cheaper and more effective to be used mainly for forest inventory in natural forests which contain large stem diameter (≥ 50–100) and high position of buttress, (≥1.8 m) with high accuracy, efficien of and low cost.